Complications in aesthetic application of hyaluronic acid in the facial area: scoping review - Quitral Argandoña , Rodrigo (2024)
Introduction: Dentists have increasingly focused on aesthetic treatments using HA, leading to a rise in associated complications and a greater need to understand its effects and management. Objective: To describe the different complications associated with the use of HA in non-surgical aesthetic procedures, as well as their management and prevention. Materials and Methods: We conducted an exploratory systematic review of existing literature on complications related to HA use in the facial area and their treatments during August 2023. PubMed, Ebsco, and Scopus were utilized for this purpose. Studies reporting complications and HA management were included, while in vitro, ex vivo, and animal studies were excluded. Results: A total of 31 articles were obtained. After screening based on titles and abstracts, 14 met the criteria for inclusion. For filler migration and lesions resembling xanthelasma, small volumes of HA are recommended. In cases of facial paralysis, hialuronidase combined with systemic or topical corticosteroids is suggested. Treatment options for late infection include laser surgery, hyperbaric oxygen therapy, drainage, broad-spectrum antibiotics, and hialuronidase, which is also used for immediate vascular complications. However, specific treatment protocols for ecchymosis, the Tyndall effect, contour irregularities, diplopia, nodules, and certain ocular complications are not well-documented in the literature. Conclusions: The most prevalent complications reported include hematoma, edema, xanthelasma-like lesions, nodules, filler migration, and erythema. Among the more complex complications, contour irregularities, ocular complications, infections, immune reactions, persistent inflammation, and vascular involvement are described. It is recommended that experimental studies be conducted to establish standardized management.